The Role of the Environmental Agency in Sustainable Waste Management in Shrimp Ponds at Padang Pariaman Beach - Bulan, Puput Sari; Mubarak , Adil (The Future of Education Journal, 2025)
Improper shrimp farm waste management has caused river and marine pollution in Pantai Padang Pariaman. This study analyzes the role of the Environmental Agency in sustainable waste management and identifies challenges in the process. Using a qualitative descriptive approach, data were collected through interviews, document studies, and observations. Informants include officials from the Environmental Agency, Fisheries Agency, shrimp farm owners, and the local community. Data analysis is based on Iyas Yusuf’s (2014) government role theory, covering three dimensions: regulator, dynamizer, and facilitator. Findings reveal that waste management remains ineffective due to limited budgets for wastewater treatment plants (IPAL) and low awareness among farm owners regarding pollution risks. Strengthening regulations, increasing owner awareness, and enhancing collaboration between the government and the community are crucial for sustainable waste management.